Existence of Solutions for Fractional Differential Equations with p-Laplacian Operator and Integral Boundary Conditions. (10th June 2020) - Xie, Jingli; Duan, Lijing
Abstract : In this paper, we investigate a class of integral boundary value problems of fractional differential equations with a p -Laplacian operator. Existence of solutions is obtained by using the fixed point theorem, and an example is given to show the applicability of our main result.